Effect of foamability on pool boiling critical heat flux with nanofluids. Issue 26 (21st June 2019) - Raza, Md. Qaisar; Kumar, Nirbhay; Raj, Rishi
Abstract : Foaming due to the presence of stabilizing agents such as surfactants deteriorates the critical heat flux (CHF) during boiling of nanofluids. A master curve is developed to demonstrate an inverse relation between CHF and the foamability. Abstract : Foaming, which is of significant importance to many industrial processes, is attributed to the reduced coalescence of bubbles due to the presence of stabilizing/foaming agents such as surfactants and nanoparticles. While foams have been extensively investigated for their rheological properties, their impact on the critical heat flux (CHF) during boiling is not well understood. The technical benefits of CHF enhancement with nanofluids are lost when surfactants are added to improve their stability. The actual mechanism of this decrease is unresolved, and thermal engineers are forced to look for alternative CHF enhancement solutions. Here, we showed that nucleating bubbles formed vapor-foam and crowded the heater surface to inhibit rewetting. Less frequent rewetting forces premature dryout, which is primarily responsible for the reported CHF deterioration. In this regime, strong foaming agents such as SDS mask the effect of nanoparticles on CHF. Using these insights, we presented a master curve that captured the effect of foamability on CHF and could be used to predict the value of CHF solely based on the foamability of the solution. We further showed that the CHF mechanism switched from the foamability regime to the conventional wettability regime upon lowering the surfactant concentration and/or with weakly foaming surfactants. In such cases, an increase in the nanoparticle concentration successfully increased CHF. We believe that the important clarifications regarding the CHF mechanism with nanofluids and the master curve of CHF versus foamability presented in this study will facilitate the design of energy-efficient boiling systems.